Pelvic ring fractures: what about timing? - Artoni, Carlotta; Pogliacomi, Francesco; Guardoli, Luca; Lasagni, Ferruccio; Leigheb, Massimiliano; Fontanesi, Francesca; Calderazzi, Filippo; Pompili, Massimo; Vaienti, Enrico; Ceccarelli, Francesco (Acta Biomedica Atenei Parmensis, 2019)
Background and aim: Pelvic ring fractures represent a challenge for orthopaedic surgeon. Their management depends on patient’s condition, pattern of fracture and associated injuries. Optimal timing for synthesis is not yet clear. The aim of this study was to define if surgical timing influenced clinic and radiographic outcomes following open reduction and internal fixation for Tile B and C fractures. Materials and methods: 38 patients were included. Patients underwent a clinical examination with the Majeed Score, Iowa Pelvic Score and Orlando Pelvic Score. The radiographic assessment was performed according to Matta Pelvic Score. A statistical analysis of the data compared patients who were operated within 3 weeks (group 1) and those operated later (group 2). Results: Both clinical and radiological outcomes were influenced by timing of surgery. Conclusion: Pelvic ring fractures interest many polytrauma patients and, therefore, their surgical orthopedic approach is frequently delayed as consequence of the severity of the associated clinical conditions. An early surgery of pelvic rong fractures allows a better quality of reduction and osteosynthesis.